Alternatives to land grabbing: exploring conditions for smallholder inclusion in agricultural commodity chains in Southeast Asia. Issue 4 (4th July 2017) - Cramb, Rob; Manivong, Vongpaphane; Newby, Jonathan C.; Sothorn, Kem; Sibat, Patrick S.
Abstract : Smallholder engagement with export commodities in Southeast Asia potentially offers a more inclusive development pathway than large-scale plantation production, which has been associated with the phenomenon of land grabs. This raises three questions which we explore in this paper: What are the agro-economic factors favouring or obstructing smallholders relative to plantations? What are the incentives for agribusiness firms to contribute to smallholder production other than by direct control of land? Can smallholder production be broadly inclusive in the face of internal differentiation and encroachment by external investors? We compare smallholder involvement with four cash crops which have experienced strong market demand – rubber, oil palm, cassava and teak – based on fieldwork in six Southeast Asian countries. We conclude that smallholder production can be a viable and inclusive strategy, contingent on the case-by-case confluence of a number of key factors which we enumerate.